Electronic Library Systems in the Focus of Digital Didactics and Cognitive Features of the Digital Generation - N. I. Gendina; E. V. Kosolapova (Библиосфера)
The relevance of the practical application of the theory of generations by N. Howe and W. Strauss in the context of digitalization is revealed. The purpose of the article is to analyze the capabilities of electronic library systems as didactic tools designed to promote the development of the cognitive abilities of the digital generation. The results of the study conducted at the Center for Interdisciplinary Cultural Studies of the Moscow State Institute of Culture are presented. The emergence of electronic library systems is characterized as a reaction to the redundancy and unreliability of information in the Internet environment. The phenomenon of the digital generation is analyzed, the maturation and socialization of which occur under the rapid penetration of digital technologies into all spheres of life of a modern person: leisure, everyday life, study, work. Representatives of this digital generation are integrated into digital society from their birth, so they have views, attitudes and values that differ from the worldview of older generations. The distinctive features and problems of developing the cognitive abilities of Z generation are considered. The results of the study of electronic educational systems “Urayt”, “Lan”, “Rukont”, “University Library Online”, “IPR Smart” are presented from the perspective of digital didactics. Violations of the didactic principles of systematic, scientific character, and clarity are identified. Recommendations are formulated for teachers and librarians on the specifics of working with Z generation.